The Chinese State, Incomplete Proletarianization and Structures of Inequality in Two Epochs - Wu Jieh-min; Mark Selden (Japan Focus)
Revolutionaries in the 1950s offered this prospect to the Chinese people: a highly egalitarian society, the product of land reform, collectivization and nationalization, with low but gradually rising income and welfare provisions for all, would chart a course toward mutual prosperity on foundations of socialist development. The key lay in restriction of markets and transfer of the surplus to the state for investment centered in heavy industry in the cities and collective agriculture in the countryside, eventually enabling China to overcome poverty and underdevelopment. This paper assesses the nature and impact of that low consumption socialist regime then and the subsequent strategies that have sustained low consumption for labor in city and countryside in the subsequent market and capitalist transition. We locate the discussion in relation to theories of original accumulation, proletarianization, wage stagnation, and low consumption in the emerging capitalist world economy of which China has been a part since the 1970s.2 We hope to add to that discussion by exploring a range of structures that have produced incomplete proletarianization and inequality during two periods of socialist transition (1950s to 1970) and capitalist transition (1970s to present).Following three decades during which China experienced the world’s most rapid growth, and in which billionaires emerged at a record rate in 2010, hundreds of millions of urban laborers, particularly the more than one hundred million migrant laborers, continue to receive not only a low but even a relatively declining share of the gross domestic product, leaving many at subsistence levels, with meager welfare benefits and bereft of basic citizenship rights.3 We use the term “laborers” to highlight the conditions of the laboring poor—rural migrant workers (nongmingong), farmers, the urban underclass, recently joined by redundant state-owned enterprise workers—examining their situation in relative as well as absolute terms. We particularly emphasize the widening income and opportunity gap separating the mass of laborers from the nouveau riche and seek to provide a structural analysis of the roots of this phenomenon. To be sure, many other nations have experienced rising social inequality in this epoch of neo-liberalism, notably the United States and Japan, but Chinese inequality has assumed distinctive forms consonant with its class structure, population control arrangements, and differential welfare policies and citizen rights. We trace and analyze these changes from the epoch of socialist transition to that of capitalist transition, while paying due attention to important continuities including the central, if changing, role of the state in shaping economic and social outcomes.Income and opportunity inequalities in the era of capitalist transition have taken distinctive new forms while growing rapidly over the last three decades. This can be clearly observed in the changing Gini coefficient and other measures of class and spatial divergence.4 But exploration of the nature of citizenship provides an important vehicle for examining broader ramifications of structures of inequality. Indeed, as in many countries, citizenship legally determines access to opportunities for income, welfare, security, education and a range of benefits presided over by the state. We dwell, however, on the distinctive forms this has taken, and continues to take, in China. The Chinese household registration system (hukou) has played a pivotal role in the “regulation” of the formation of the working class under conditions of free and unfree markets, in ways that invite comparison with the Act of Settlement in England prior to the era of the Speenhamland system, which hindered the movement of rural labor.5 The hukou regime has imposed conditions of severe inequality on migrants and their families, initially in the years 1960 to the late 1970s when rural to urban migration and market activity were virtually foreclosed, but also in the subsequent era when the state encouraged migration and market activity, while maintaining differential access to education, health care, retirement pensions etc., distinguishing those “sojourning” in the cities from those with full urban citizen rights on the basis of hukou.6Less studied, but equally important, in our view, is the interrelationship between inequality, on the one hand, and savings and underconsumption, on the other. We consider the mechanisms that have led to high savings and resource transfer to the state during both the revolutionary era (1949-1970s) and the era of capitalist transition (1970s-present). We probe mechanisms that led to high savings and low consumption for Chinese working people during both periods, including those imposed by the state and those that are market driven and/or the consequence of a paucity of welfare benefits, particularly as these impinge on the laboring poor in city and countryside. Specifically, we explore the relationship between high savings and structures of inequality and consider their consequences for Chinese trajectories of development, incomplete proletarianization, and social polarization.